2019
DOI: 10.1002/adbi.201900131
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds Are Involved in Cellular Crosstalk and Upregulation

Abstract: Cell–cell cross talk is of great importance in cancer research due to its major role in proliferation, differentiation, migration, and influence on the apoptotic pathway. Different cell–cell communication mechanisms have come mainly from proteomic and genomic approaches. In this paper, a new route is reported for cross talk between cancer cells that occurs, even when they are far away from each other. Single‐cell and culture analysis shows that upregulation of cancer cells emits hundreds of volatile organic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…However, it provides preliminary proof for the feasibility of skin VOCs to serve as TB‐associated probe molecules. Furthermore, GC‐MS analysis can be used for investigation of the metabolic processes and their relation to VOCs, [ 18,19 ] and work up the nanomaterial‐based sensors and algorithms for better performance. [ 15,20 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it provides preliminary proof for the feasibility of skin VOCs to serve as TB‐associated probe molecules. Furthermore, GC‐MS analysis can be used for investigation of the metabolic processes and their relation to VOCs, [ 18,19 ] and work up the nanomaterial‐based sensors and algorithms for better performance. [ 15,20 ]…”
Section: Resultsmentioning
confidence: 99%
“…In general, during disease formation, cells undergo structural and metabolic changes that change VOC patterns. [ 18,19,21 ] As a result, some of these VOCs appear in distinctive compositions of the mixture, depending on whether a cell is healthy or infected. [ 22–24 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most recent discoveries in the field of origins and nature of VOCs is the finding that they serve as cell-to-cell communication. In a novel study by Serasanambati et al 27 they proved for the first time in reported literature how cancer cells can induce changes in the phenotype of neighboring cells through the upregulation of VOCs. Among other interesting experiments, they co-cultured in an in-vitro fashion normal lung cells and tumoral cells, which shared their headspace but were physically unconnected.…”
Section: Vocs: What and Whymentioning
confidence: 99%